Removal of Dyes by Polymer-Enhanced Ultrafiltration: An Overview - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The current problem of contamination caused by colored industrial effluents has led to the development of different techniques to remove these species from water. One of them, polymerenhanced ultrafiltration (PEUF), has been systematically studied in this mini review, in which research works from 1971 to date were found and analyzed. Dye retention rates of up to 99% were obtained in several cases. In addition, a brief discussion of different parameters, such as pH, interfering salts, type of polymer, dye concentration, and membrane type, and their influence in dye removal is presented. It was concluded from the above that these factors can be adapted depending on the pollutant to be remediated, in order to optimize the process. Finally, theoretical approaches have been used to understand the intermolecular interactions, and development of the studied technique. In this revision, it is possible to observe that molecular docking, molecular dynamics simulations, density functional theory calculations, and hybrid neural-genetic algorithms based on an evolutionary approach are the most usual approximations used for this purpose. Herein, there is a detailed discussion about what was carried out in order to contribute to the research development of this important science field. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.